TASHKENT IN THE VERSES OF ALEXANDER ARKADYEVICH FAINBERG - Toshtemirova Kamola Vakhobjon kizi; Sogukpinar Dilorom Alimovna (Proximus Journal Publishing, 2025)
The article is devoted to the analysis of the image of Tashkent in the poetry of Alexander Arkadyevich Fainberg (1939–2009), a Russian-language poet and People's Poet of Uzbekistan. Through the examination of his poems, the article explores how the city embodies the meeting of Russian and Uzbek cultures, becoming a living symbol of memory, everyday life, and spiritual synthesis in the poet's work
Keywords: poet of two nations; translator; poem